The housing Phillips curve and momentum in the Norwegian housing market - Sara Jahr Kirkeby; Plamen T. Nenov (Norges Bank, 2023)
This paper provides descriptive evidence for a housing Phillips curve in Norway, suggesting a negative relationship between the ratio of inventory-to-sales and subsequent house price growth in the market for existing homes. We show that the negative relationship between inventory-to-sales and house price growth in Norway only holds at short horizons, consistent with short-term momentum in the Norwegian housing market. This is in contrast to the U.S. housing market, where the Phillips curve relationship and momentum effects persist over longer horizons. We also examine heterogeneity in the housing Phillips curve and momentum across Norwegian local housing markets and find that the housing Phillips curve is stronger in larger cities. Overall, our findings imply that the Norwegian housing market is less frictional than the U.S. housing market, with homes selling faster on average and house prices responding faster to shocks.
hdl:11250/3073124
Keywords: 330; House prices; dynamic housing Phillips curve; house price momentum; local projections; months-of-supply; financial stability